2013
DOI: 10.1002/aic.13986
|View full text |Cite
|
Sign up to set email alerts
|

Fluid‐phase coexistence for the oxidation of CO2 expanded cyclohexane: Experiment, molecular simulation, and COSMOSAC

Abstract: The gas solubility of pure oxygen and of pure carbon dioxide as well as of their gaseous mixture are measured in the ternary liquid mixture cyclohexane 1 cyclohexanone 1 cyclohexanol at 313.6 K with a high-pressure view-cell technique using the synthetic method. The new experimental data are used to assess the capability of molecular simulation and conductor-like screening model (COSMO)-SAC to predict multicomponent fluid-phase coexistence behavior. These methods are also compared systematically on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Supercritical carbon dioxide (ScCO 2 ) is widely used in industry, such as for extraction of natural flavors, decaffeination of coffee beans, or as a solvent in polymer synthesis processes [1][2][3][4][5][6][7][8]. Sometimes cosolvents are necessary either to increase the solubility of the solute in ScCO 2 or to modify the properties of ScCO 2 .…”
Section: Q2mentioning
confidence: 99%
“…Supercritical carbon dioxide (ScCO 2 ) is widely used in industry, such as for extraction of natural flavors, decaffeination of coffee beans, or as a solvent in polymer synthesis processes [1][2][3][4][5][6][7][8]. Sometimes cosolvents are necessary either to increase the solubility of the solute in ScCO 2 or to modify the properties of ScCO 2 .…”
Section: Q2mentioning
confidence: 99%
“…. These equations of state can apply to predict the phase equilibrium and solubility by combining them with a predictive liquid model 29,[54][55][56] , such as UNIQUAC Functional-group Activity Coefficients (UNIFAC) 57 or Conductor-like Screening Model-Segment Activity Coefficient (COSMOSAC) 58,59 . In this study, two correlative approaches based on PR EoS were used to model the palbociclib solubility data:…”
Section: Solubility Correlation and Prediction Using Cubic Equation O...mentioning
confidence: 99%
“…For mixtures containing a supercritical component, a straightforward approach is to combine the COSMO-SAC model with a cubic equation of state (EOS), such as the Peng–Robinson (PR) EOS or its modified version by Stryjek and Vera (PRSV EOS), through an excess Gibbs free energy G ex based mixing rule, such as the modified Huron–Vidal first-order (MHV1) mixing rule or the Wong–Sandler (WS) mixing rule. , In several publications, this approach was assessed for these two mixing rules, because they are classical and are widely used in industrial applications. Thus, the second goal of this study was to evaluate the predictive power for mixtures of type CO 2 + C1–C5 alcohols on the basis of these two mixing rules, that is, PRSV + MHV1 + COSMO-SAC and PRSV + WS + COSMO-SAC. It has been shown that the accuracy of this approach can be improved significantly with the introduction of binary interaction parameters; however this was not the focus of this study. Finally, a case study on drug solubility in CO 2 + ethanol mixtures was conducted to demonstrate a potential application of these two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical carbon dioxide (ScCO 2 ) has a wide variety of applications in chemical, food, and pharmaceutical industries. For example, ScCO 2 is used as a solvent for the decaffeination of coffee beans, the extraction of natural flavors, or as a reaction medium in polymer synthesis processes. However, since ScCO 2 has a limited capability (even at high pressures) for the extraction of polar solutes, , low molar mass alcohols are added as cosolvents for increasing their solubility. , The fluid phase behavior of CO 2 + low molar mass alcohol mixtures is thus crucial for the design and optimization of extraction processes that contain these alcohols as cosolvents. To the best of our knowledge, vapor–liquid equilibrium (VLE) data for all CO 2 + C1–C5 alcohols are available in literature, except for CO 2 + 2,2-dimethyl-1-propanol (CAS No.…”
Section: Introductionmentioning
confidence: 99%